Natural variations in the promoter of Awn Length Inhibitor 1 (ALI‐1) are associated with awn elongation and grain length in common wheat. (4th December 2019) - Wang, Dongzhi; Yu, Kang; Jin, Di; Sun, Linhe; Chu, Jinfang; Wu, Wenying; Xin, Peiyong; Gregová, Edita; Li, Xin; Sun, Jiazhu; Yang, Wenlong; Zhan, Kehui; et al.
Summary: Wheat awn plays a vital role in photosynthesis, grain production, and drought tolerance. However, the systematic identification or cloning of genes controlling wheat awn development is seldom reported. Here, we conducted a genome‐wide association study (GWAS) with 364 wheat accessions and identified 26 loci involved in awn length development, including previously characterized B1, B2, Hd, and several rice homologs. The dominant awn suppressor B1 was fine mapped to a 125‐kb physical interval, and a C2 H2 zinc finger protein Awn Length Inhibitor 1 ( ALI‐1 ) was confirmed to be the underlying gene of the B1 locus through the functional complimentary test with native awnless allele. ALI‐1 expresses predominantly in the developing spike of awnless individuals, transcriptionally suppressing downstream genes. ALI‐1 reduces cytokinin content and simultaneously restrains cytokinin signal transduction, leading to a stagnation of cell proliferation and reduction of cell numbers during awn development. Polymorphisms of four single nucleotide polymorphisms (SNPs) located in ALI‐1 promoter region are diagnostic for the B1 / b1 genotypes, and these SNPs are associated with awn length (AL), grain length (GL) and thousand‐grain weight (TGW). More importantly, ali‐1 was observed to increase grain length in wheat, which is a valuable attribute of awn on grain weight, aside from photosynthesis. Therefore, ALI‐1 pleiotropically regulates awn and grain development, providing an alternative for grain yield improvement and addressing future climate changes. Significance Statement: We systematically identified the loci controlling wheat awn length at genome level, and cloned the ALI‐1 underlying major awn inhibitor B1 . Natural variations in the promoter of ALI‐1 are associated with awn elongation and grain length in common wheat, providing explanations for the effects of wheat awn on grain production. This work provides an alternative to achieve improved grain yield and address future extreme climates.